BULYYING BEHAVIOR IN YOUTH IN WEST SUMATRA PROVINCE - Zikry Latupasjana; Neviyarni Neviyarni; Marjohan Marjohan; Afdal Afdal (Jurnal Neo Konseling, 2022)
The problem of bullying has increased in recent years, especially for vocational students in the province of West Sumatra, this study will examine the problems in how the characteristics, factors, impacts, and efforts have been made by BK teachers and the school in overcoming bullying behavior. The type of research used is descriptive quantitative. The data of this research are counseling guidance teachers, students of Vocational Schools of West Sumatra Province. Data collection techniques, interviews, through questionnaires and research results, bullying that occurs in vocational students in the province of West Sumatra is in the moderate category with a percentage of 41%. Guidance and counseling has an important function in overcoming problems that occur, with various counseling guidance services expected to be able to prevent bullying from occurring in the school environment.